Delocalized positronium in alkali halides - Boev O. V. (1984, 1984)
The Bloch state of positronium in alkali halide crystals is considered. Interactions of positronium with the crystal field and with acoustic phonons are taken into account using perturbation theory. The effective mass of positronium in alkali halides is determined theoretically for the first time. Influence of these interactions on the positronium features in a crystal is discussed. The results obtained are in good agreement with available experimental data.